Implementation Of Advanced Manufacturing Technologies (Amts) In The Small And Medium Scale Industries (Smis) Of Malaysia - Mohd. yusuff, Rosnah (2002)
The implementation of advanced manufacturing technology (AMT) has been known to increase the competitiveness of manufacturing firms. For the small and medium scale industries (SMIs), the implementation of AMT is necessary to face the challenges of globalization and to ensure their future survival. However, studies have shown that the full potential of AMT can only be realized if certain requirements are in place before embarking on AMT implementation. The competitive benefits can be fully acquired if there is alignment between the technology and organization. Thus, the implementation of AMT requires not only technological change, but also supported by operational and organizational change.This study evaluates the ability and capabilities of the Malaysian SMis to implement AMI successfully. The current level of technology, the organizational and managerial capabilities of the SMIs were investigated to determine the extent of 'alignment' or 'misalignment' between technology and organization. By identifying the gap of the 'misalignment', the necessary steps can be taken to close this gap. A survey questionnaire was developed to meet the objectives of the study. A total of 1182 companies were included in the sample, and only 136 (-12%) companies responded. The results were analysed using the Statistical package for Social Science (SPSS) for mean values, percentages and correlation coefficients. To determine the 'gap' between technology and organization, a regression analysis was conducted to find the 'best fit curve'. The results showed that among the AMTs implemented, CAD and PLC were the most commonly used and adopted by about 25% of the companies. Other AMTs were used by less than 25% of the companies. It was found that, overall, the business techniques have greater emphasis compared to the engineering and manufacturing techniques, especially for the AMT that are in place and in progress. The companies showed a greater tendency for software based AMTs. The technologies implemented can be classified as 'stand alone' or level one AMT against the level four or fully integrated systems signified by the least common technologies implemented. Computer controlled equipment is hardly used and integration of functions through computer systems is very low. The companies showed a higher usage of computers for the business functions rather than in production.